The credit risk and its impact on the efficiency of credit portfolios in commercial banks An Analytical study on private banks in Syria - المملوك, أنس هشام (Latakia University Journal - Economic and Legal Sciences Series, 2020)
This research aims to analyze the impact of the total credit risks to which the credit portfolios of the Syrian private banks are exposed, by analyzing the basic ratios that indicate the efficiency of the credit portfolio and linking them with the total credit risk exposures, in order to arrive at knowledge of the efficiency of these banks in managing this type of risk, Three of the banking financial ratios recognized in this field have been analyzed to measure the efficiency of the credit portfolio and its relationship to the degree of its risks. Perhaps the most important of these are the accounting measures derived from the financial statements of banks, and the most important of these measures are the non-performing debt coverage ratio, the guarantee coverage ratio, the asset efficiency measurement ratio. these ratios were analyzed by a quantitative sectorial analysis based on the statistical study to link the research variables, and a qualitative sectorial analysis that directly measures the degree of efficiency of the credit portfolios of the studied banks within the sample by giving a degree of efficiency commensurate with the average measurement of these ratios in order to reach the optimum measure for the size of total exposure to risks Fiduciary. The research sample included eleven private Syrian banks during the period from 2008 to 2018 in order to find a relationship between the independent variables and the dependent variable in the research, by using the method based on the Eviews statistical analysis program to analyze the relationship between those variables. The research concludes that there is a varying effect between the total exposure to credit risk and the efficiency of the credit portfolios of banks. The research also showed the importance of maintaining the composition and quality of the credit portfolio, and reducing its risks within acceptable levels.